Modern seismicity in Northern Algeria: performance of local networks and evolution compared to the historical seismicity. - Bouhadad, Youcef (2022)
During the past decades, there was a remarkable rebound in seismicity studies in northern Algeria, where almost all moderate earthquakes were thoroughly studied and result published. This fact was made possible by the deployment, extension and modernization of local seismological networks. In this work, 20 earthquakes (4.5 ≤ Mw ≤ 5.9) occurred in the Tell Atlas of Algeria for the period (2006–2021) and recorded by many digital stations of the national accelerograph network are considered. First, we located hypocenters of the events. Second, we performed a waveforms inversion of accelerograms to describe the seismic source (seismic moment, moment magnitude and focal mechanisms of the corresponding earthquake). The hypocenters are well constrained better than those provided by international organisms, while the magnitudes and focal mechanisms are comparable. In the western Tell Atlas, the focal mechanisms often yielded reverse faulting, while in eastern Algeria, they showed often strike slip solutions. The instrumental seismicity often occurred inside or around Neogene basins, known already to have experienced historical seismicity.